Analysis of Magneto Hydrodynamic of Second Order Fluid Flow in a Micro- Channel and heat Transfer between Two Parallel Plates - Wala’a Abdul Mageed Mahdi (Journal of Madenat Alelem University College, 2016)
In present study, analysis of magnetic field was studied in the state of non Newtonian fluid of second order flows and heat transfer in micro channel between two parallel plates, introduced. The equations are used to describe the flow are the motion and the energy equations. It found that these equations are controlled by many dimensionless numbers such as Reynolds number (Re), magnetic field parameter (M), physical quantity at wall (W), Knudsen number (Kn), Peclet number (Pe), Brinkman number (Br) and the material of fluid ( . The homotopy analysis method (HAM) is used to obtain the analytic solution for the velocity and heat transfer, the effect of each dimensionless parameters upon the velocity and heat distribution is analyzed and shown graphically by using MATLAB package.